Padrões na pesquisa de ecologia de sementes no Pantanal : lacunas, vieses e consequências para a restauração - Gonçalves, Driele Silva de Amorim (2022)
Studies on seed ecology provide a required knowledge for effective ecological restoration management. Geographic and taxonomic biases are prevalent on seed ecology research in Brazil, where resulting knowledge gaps limit the application of appropriate conservation policies. The Pantanal, the world’s largest tropical wetland, is increasingly suffering anthropogenic disturbance of native vegetation during the last decades, but studies on seed ecology and restoration programs of the different habitats of this biome are neglected. The objective of this work is to evaluate the knowledge (geographic, taxonomic and ecological biases, gaps and patterns) of studies on seed ecology of native plants in the Pantanal biome, quantifying and evaluating the scientific production on this topic from a survey of publications in scientific journals. After searching publications in both the Scielo and the Web of Science, a database comprising 39 articles, 395 species, 82 families and 2584 cases was generated for the topics related to seed ecology: pollination and seed set, dispersal, dormancy, seed bank, removal, predation, germination, seedling establishment and tolerance. We identified extensive sampling data in the Brazil’s southern Pantanal, while the Pantanal biome in Paraguay remained unexplored. Some families and species were oversampled, while others were undersampled. The studies were mostly conducted in terrestrial areas. The species studied were most commonly herbs or shrubs, occurring in terrestrial substrates, dry fruit, and with zoochoric dispersal. Dispersal and germination were the most studied topics and dormancy was little explored. Our data suggest that the deficit of knowledge on seed ecology in the Pantanal hinders an appropriate restoration plan and consequent progress to achieve the targets of Agenda 2030 in Brazil. We propose an expansion of research and improvement of databases on wetland plant seeds in order to promote successful restoration programs.